DIAGNOSIS OF HUMAN PARVOVIRUS B19 ASSOCIATION RHEUMATOID ARTHRITIS BY RT-PCR - Doaa Ali Saeed; Fadyia Mahdi Muslim Alameedy (Scholar Express Journals, 2022)
Human samples of human Parvovirus B19 were collected during October, 1st, 2020 to 15 of February 2021. Human Parvovirus B19 was including (25 - 68 years). The RT-PCR. method was detected of all samples , the results showed seventy (70%) while thirty (30%) negative cases. The Population groups studied samples subject groups were distribution into (4) groups including (25-35, 36-46 and 47-57 and 58-68) year, changed age too gender. The third groups (47-57 years ) were high cases of human infected (51.43%) in compare of aged groups then [36-46 (20%) ; 58-68 (18.57%) ; 25-35 (10%) years]. The percentage of females(70%) is higher than males (30%) .The samples were isolated from the hospitals including ( Al-Sadr , AL Hakeem , Middle of Euphrates). The first study in Iraq to diagnose of human Parvovirus B19 with rheumatoid arthritis
Keywords: Parvovirus B19; Rheumatoid arthritis; erythroid progenitor cells; Real time PCR